The impact of term-time paid work on academic performance in nursing students: A longitudinal study - Salamonson, Y.; Everett, B.; Koch, J.; Andrew, S.; Davidson, Patricia (Pergamon, 2012)
Background: Nursing students in higher education are spending more time in paid employment despite evidence that this can impact negatively on academic performance. Objectives: To examine the effect of paid work on academic performance in undergraduate nursing students. Design: Descriptive, correlational survey with longitudinal follow-up. Participants: Nursing students in metropolitan Sydney, Australia. Methods: First year nursing students surveyed at baseline were followed up at the end of the final year of their nursing program to examine factors influencing academic performance. Results: Of the 566 Year 1 nursing students who were surveyed in the second semester of their Bachelor of Nursing program, 182 students (32%) completed the follow-up survey in Year 3. The percentage of students engaging in paid work during term-time had increased (p < 0.001), from 70% in Year 1 to 84% in Year 3. There was an inverse relationship between mean hours in paid work during term-time and nursing students’ GPA in their final year. Taking into account demographic factors, the mean hours spent in paid work during term-time had a negative impact on nursing students’ GPA (p < 0.001). Conclusion: In view of these findings, we suggest that new models of undergraduate nursing education be explored to include faculty approved nursing-related employment with defined opportunities for learning. This would accommodate the dual roles of undergraduate nursing students as students and employees and therefore not endanger their academic performance.